Facilitating Genetics Aware Clinical Decision Support: Putting the eMERGE Infrastructure into Practice - Taylor, Casey Overby; Rasmussen, Luke V.; Rasmussen-Torvik, Laura J.; Prows, Cynthia A.; Dorr, David A.; Samal, Lipika; Aronson, Samuel (ACI Open, 2021)
This editorial provides context for a series of published case reports in ACI Open by summarizing activities and outputs of joint electronic health record integration and pharmacogenomics workgroups in the NIH-funded electronic Medical Records and Genomics (eMERGE) Network. A case report is a useful tool to describe the range of capabilities that an IT infrastructure or a particular technology must support. The activities we describe have informed infrastructure requirements used during eMERGE phase III, provided a venue to share experiences and ask questions among other eMERGE sites, summarized potential hazards that might be encountered for specific clinical decision support (CDS) implementation scenarios, and provided a simple framework that captured progress toward implementing CDS at eMERGE sites in a consistent format.
Keywords: editorial; case report; genomics; pharmacogenomics; clinical decision support requirements; gathering information technology; infrastructure